Funcionamento ecossistêmico e exploração florestal em uma área de manejo de impacto reduzido na Floresta Amazônica brasileira - Senna, Norma Rodrigues Nunes de (2021)
Tropical regions are extremely species-rich ecosystems and play an essential role in regulating biogeochemical cycles. The Amazon Rainforest represents the largest remaining area of intact tropical rainforest and the most species-rich biome on Earth. Despite their great importance, large-scale environmental changes, including changes in land use and climate change, threaten these and many other ecosystem services provided. Selective logging is considered the most widespread land use change in tropical ecosystems and a promising way to avoid Amazon devastation is the development of low-impact forest management, using techniques that reduce impacts on the environment. In order to understand the effects of functional characteristics on forest exploitation and the impact on aboveground biomass and forest carbon stocks, we assess how different types of logging influence the characteristics that maximize ecosystem functioning and those that maximize forest exploitation. The study was carried out in the Caxiuanã National Forest, in the state of Pará, in a low-impact Forest Management area. We carried out a forest census, where all living tree species with diameter at breast height ≥ 32 cm were sampled, totaling 32.926 individuals, belonging to 117 species. We also analyzed characteristics such as stem quality and height, wood density, aboveground biomass and carbon stock and subdivided species into class according to exploitation potential (ie substitutes, exploited and unexploited).We verified a relationship between aboveground biomass (AGB) and functional traits of Ecosystem Functioning, negatively affected by richness and functional evenness, indicating that the more similar the functional traits of the species, the greater the forest biomass. As for the functional diversity indices measured by functional richness (FRic) and functional evenness (FEve), we found a positive effect for Ecosystem Functioning, when we maintain the interesting functions for Forest Exploitation. As an important application for conservation, our result indicates that public policies aimed at protecting forest biomass, such as REDD+, are not sufficient to guarantee the protection of forest biodiversity, as areas with high AGB values have little functional diversity.